Business environment analysis of Romania - Darius Stan (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 5th Edition of the International Symposium, November 2014, Bucharest, 2014)
For much of human history, most people have been deprived of liberty without economic and investment opportunities being driven by poor living. Today, however, say that living in the most prosperous in history. In trying to remove poverty, disease, ignorance around the world, given the fact that in large part, the restriction on economic freedom is an important obstacle in trying to define an array in this analysis of the economic potential enlightening in the economic freedom in Romania. In 2014, the principles of economic freedom were again measured and collected in the Index of Economic Freedom, the source directories published by The Wall Street Journal and The Heritage Foundation. We also sought to highlight in an easy to use analysis, we can easily track progress in the development of Romania for economic openness, prosperity, opportunity. The paper will reveal the elementary analysis of the 10 freedoms - from property rights to entrepreneurship - in a report than 186 countries.
Keywords: 330; economic freedom indicators; opportunity; poverty; investment